FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Ayu Babro Valentina; Putu Kepramareni; Ni Luh Gede Mahayu Dicriyani (KRISNA: Kumpulan Riset Akuntansi, 2022)
This researchaims to find out the influence tax understanding, tax socialization, taxpayer awareness, tax sanctions and tax employee services to taxpayercompliance. The population in the study was all motor vehicle taxpayers registered with the Technical Implementation Unit of the Bali Provincial Levy Tax Service in Karangasem Regency in 2020 as many as 211,821 motor vehicle taxpayers with samples used, namely as many as 100 respondents determined by incidental sampling method. The data analysis technique used in this study is multiple linear regression. The results showed that tax understanding, tax socialization, taxpayer awareness, tax sanctions and tax employee services had a positive and significant effect on taxpayer compliance.